The Physics of Pneumatic Tide Gauges - Pugh, D. T. (The International Hydrographic Review, 2015)
As a part of its programme to monitor sea level around the British Isles, the Institute of Coastal Oceanography and Tides has a requirement for a recording system which may be quickly and easily installed, and which gives results accurate to 0.01 metre. The traditional stilling-well installation, apart from being costly and difficult to install on a temporary basis, has a number of fundamental disadvantages which limit its ability to record true water levels accurately (Lennon , 1971). Furthermore, stilling-wells, may only be installed where a harbour wall, pier or other vertical structure exists, and such structures are seldom located in positions which are representative of open sea conditions. Pneumatic pressure tide gauges have a number of advantages : not only may they be easily installed on vertical structures, but they may also be used on open coast lines, along beaches, or wherever a light connecting tube can be run from an underwater gas outlet to a recorder ashore. By comparison with gauges which rely on submerged electrical transducers connected to a shore-based recorder by conducting cable, the vulnerable underwater parts of pneumatic gauges are both cheap and easily repaired. Before adopting the pneumatic tide gauge principle for routine measurements it was necessary to investigate the physics of such systems, so that sources of error could be eliminated or subject to correction. This report contains details of these investigations; their application to coastal sea level measurements is described in more detail elsewhere (Pugh, 1971). Details of the bubbler-type gauge which uses a continuous flow of air through a connecting tube to an underwater outlet are given in the first section. However, an extension of the bubbler-gauge theory shows that a flow of air is not strictly necessary, and details of a non-bubbling system are given in the second section. This latter type of gauge is similar to gauges which use a partially inflated bag, but it has the advantage that gauge datum is defined to the same accuracy as a bubbler-gauge datum. The third section of this paper shows how these results may be applied to the design of actual pneumatic tide gauge systems.